How Does She Learn English? A Case of a Successful Blind Language Learner - Jafari, Sakineh; Jafari, Samaneh; Kafipour, Reza (Vision: Journal for Language and Foreign Language Learning, 2020)
This study reports on a case study of a blind EFL learner. The purpose of the study was to explore a detailed situated data to examine to what extent it is feasible to be a successful language learner despite being visually impaired and lacking some learning resources.Â  Interview data and the narratives of this EFL learner have revealed that her success was mainly based on her agentic interaction with the environment and learning context, her high motivation and strategic behavior, and her sustained efforts. The findings provide further insight into the role of learner in exerting control over contextual resources that frame learning and on how different factors interact with each other in the language learning process in the construction of learner identity and the strategies used by learners.